Neural Tube Defects - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
In an overview of neural tube defects (NTD's), Dr RJ Lemire of the Dept Pediatrics, Univ of Washington and Children's Hospital, Seattle, WA, divides them into two major groups: (1) neurulation and (2) postneurulation defects.